Subtyping of STEC by MLVA in Argentina - Bustamante, Ana V.; Sanso, Andrea M.; Parma, Alberto E.; Lucchesi, Paula M. (Frontiers in Cellular and Infection Microbiology, 2012)
Shiga toxin-producing Escherichia coli (STEC) causes serious human illness such as hemolytic uremic syndrome (HUS). Argentina has the world’s highest rate of this syndrome, which is the leading cause of acute renal failure among children. E. coli O157:H7 is the most common cause of HUS, but a substantial and growing proportion of this illness is caused by infection due to non- O157 strains. Multiple-locus variable-number tandem repeat analysis (MLVA) has become an established technique to subtype STEC. This review will address the use of routine STEC subtyping by MLVA in order to type this group of isolates and to get insight into the genetic diversity of native STEC. With regard to these objetives we modified and adapted two MLVA protocols, one exclusive for O157 and the other, a generic E. coli assay. A total of 202 STEC isolates, from different origin and corresponding to 20 serotypes, have been MLVA genotyped in our laboratory. In our experience, MLVA works well at our laboratory and enables us to perform an efficient STEC subtyping. The diversity found in many serotypes may be useful for future epidemiological studies of STEC strains, belonging to O157 as well as to non-O157 serogroups.